An Analytical Framework for the Assessment of Goals and Approaches by the Iraqi Airways Company - Noor Abdulameer Kareem Al-Muthanna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
For the purpose of assessing Iraqi Airways Company's goals and tactics, we presented a mathematical model in this article. We began by looking at Iraqi Airways' timetables, which provide many departure cities for each route. The optimal route for the airline was then determined by using certain fuzzy integrals